Editorial - Teddy Surya Gunawan (International Islamic University Malaysia Engineering Journal)
The IIUM Engineering Journal, Vol. 25 No. 1, showcases a diverse array of pioneering research that pushes the boundaries of engineering and technology. This issue reflects a commitment to addressing critical challenges, exploring innovative solutions, and advancing sustainable practices across various disciplines. From air pollution modeling and flood mapping to groundbreaking healthcare and renewable energy applications, this edition captures the essence of interdisciplinary collaboration and ingenuity.